2000
DOI: 10.1074/jbc.m000759200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Phosphoinositide 3-Kinase Pathway Induces a Senescence-like Arrest Mediated by p27Kip1

Abstract: A senescence-like growth arrest is induced in mouse primary embryo fibroblasts by inhibitors of phosphoinositide 3-kinase (PI3K Kip1 can induce permanent cell cycle arrest and a senescence-like phenotype in wildtype mouse embryo fibroblasts. We also obtained results suggesting that the kinase inhibitors LY294002 and Wortmannin arrest cell growth and induce a senescence-like phenotype, at least partially, through inhibition of PI3K and protein kinase B/Akt, activation of the forkhead protein AFX, and up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
182
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(205 citation statements)
references
References 63 publications
19
182
1
3
Order By: Relevance
“…Expression of transfected p27 KIP1 was assessed by Western blotting (results not shown). As described in other cell systems [37,38], constitutive overexpression of p27 KIP1 resulted in the acquisition of a senescent-like phenotype in about 60 % of transfected cells (results not shown).…”
Section: Modulation Of Cdk2 Activity By Bcl-2supporting
confidence: 76%
See 1 more Smart Citation
“…Expression of transfected p27 KIP1 was assessed by Western blotting (results not shown). As described in other cell systems [37,38], constitutive overexpression of p27 KIP1 resulted in the acquisition of a senescent-like phenotype in about 60 % of transfected cells (results not shown).…”
Section: Modulation Of Cdk2 Activity By Bcl-2supporting
confidence: 76%
“…In addition, direct inhibition of Cdk2, by means of a dominantnegative kinase, results in the acquisition of a senescent-like phenotype in a large fraction of H1299 cells. A contribution of p27 KIP1 to the onset of senescence has previously been suggested in primary mouse fibroblasts treated with phosphoinositide 3-kinase inhibitors [38]. Furthermore, p27 KIP1 protein appears to be accumulated during senescence in human fibroblasts [44].…”
Section: Induction Of a Senescent-like Phenotypementioning
confidence: 77%
“…In fact, the PI3K inhibitor LY294002 has been observed to induce both G 1 and G 2 /M arrests (Figure 1e; Collado et al, 2000). According to previous studies, LY294002-induced G 1 arrest is considered to be due to activation of p21 CIP1 and p27 KIP1 , whereas G 2 /M arrest by the inhibitor may occur as a result of WEE1Hu activation in addition to p21 CIP1 and p27 KIP1 (Collado et al, 2000;Rodier et al, 2001;Zhou et al, 2001;Fujita et al, 2002;Katayama et al, 2005). Matsushima-Nishiu et al (2001) have shown that adenoviral transduction of the PTEN gene product induces p15 INK4b mRNA expression as same as p27 KIP1 mRNA expression, as seen on DNA microarray and RT-PCR analyses.…”
Section: Discussionmentioning
confidence: 99%
“…p27 KIP1 is a target of transcription by FOXOs Stahl et al, 2002), and it induces cell-cycle arrest in any phase. In addition, the functions of p21 CIP1 and p27 KIP1 are inhibited by Aktdependent phosphorylation and translocation from nuclei to cytoplasm (Collado et al, 2000;Rodier et al, 2001;Zhou et al, 2001;Fujita et al, 2002). Thus, activation of the Akt signaling pathway can avoid cellcycle arrest of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have provided evidence for a role for the PI-3-kinase pathway in senescence. In cultured mouse embryonic fibroblasts, the PI-3-kinase inhibitors LY294002 and wortmannin induce senescence (Collado et al, 2000). In mouse models of melanoma, whereas BRAF activation in melanocytes mimics the generation of senescent cells described in human naevi, BRAF activation in mice deleted for PTEN leads to the formation of malignant tumors (Dankort et al, 2009).…”
Section: Introductionmentioning
confidence: 99%